THE ABILITY OF THE FIRST YEAR STUDENTS OF SMKN 2 PARIAMAN IN WRITING INQUIRY LETTERS - Latifah Turrahmah; Rusdi Rusdi; Don Narius (Journal of English Language Teaching, 2017)
This research is about students’ ability in writing a business letter, especially an inquiry letter. This research was aimed at analyzing students’ ability in writing inquiry letters deal with its letter organization. This research used descriptive research. The population of this research were all of the first year Office Administration students from two classes, X AP1 and X AP2. There were seventy-four students. The samples were twenty-five students taken by using random sampling technique. The instrument applied in this research was a written test about inquiry letter. Students were asked to write inquiry letter based on three topics that they have chosen in the previous week for sixty menutes. The data was analyzed by using a rubric score of the inquiry letter deal with its letter organization. The result of this research showed that students got 4 (well) in writing the inquiry letter deal with its letter organization. However, there were some organization of letter that did not write properly. Students were expected to have more understanding in writing a proper inquiry letter deal with its letter organizaton